An intelligent approach in parking system for car parking guidance and damage notification in light of GPS - Nagabhushana Rao, M; Kumar Raja, P; Ravi chand, S; AkruthJames, P (International Journal of Engineering and Technology, 2018)
Every motorist dreams for a vehicle which can stop itself with negligible help from the driver. This paper introduces a smart approach in stopping framework (IPS) that has two capacities: Car stopping direction and auto harm notice. IPS is a propelled programmed driving framework which offer stationed support to the vehicle drivers when the vehicle has been stopping. Intelligence parking system (IPS); adjusts the intrigue responsibilitieswhichsurety smooth stopping, by empowering GPS construct application that keeps running in PDA light whichfacilitates the vehicle drivers for detecting theremote placing spot, wig out harms, stopping inside an appropriate spots in very low time & grasping a warning when it stopped auto can be harmed when there is no person in that auto or vehicle. Amid stopping procedure, person has alarmed with the help of perceptible and signals of sound. A harm warning framework encompasses the vehicle or auto; camera and sensors at before and back side of an auto/vehicle which observes the all the things even the drive is not there.
Keywords: Control Car System; Path Planning; Client Device; Damage Notification